MiR-221 and miR-222 synergistically regulate hepatocyte growth factor activator inhibitor type 1 to promote cell proliferation and migration in gastric cancer. Issue 6 (May 2017) - Ning, Tao; Zhang, Haiyang; Wang, Xinyi; Li, Shuang; Zhang, Le; Deng, Ting; Zhou, Likun; Wang, Xia; Liu, Rui; Bai, Ming; Ge, Shaohua; Li, Hongli; et al.
Gastric cancer is a common malignancy with limited treatment options and poor prognosis. Introduction of novel pathways of gastric cancer will provide candidates for target therapy. Hepatocyte growth factor activator inhibitor type 1 is an integral-membrane proteinase inhibitor. Hepatocyte growth factor activator inhibitor type 1 abnormality is found in various cancers and correlates with tumor progression and metastasis. However, the mechanisms underlying the dysregulation of hepatocyte growth factor activator inhibitor type 1 expression in gastric cancer remain unclear. Although microRNAs have been reported to be involved in the development of cancer, the roles of miR-221 and miR-222 in gastric cancer have not been reported yet. In this study, we showed that hepatocyte growth factor activator inhibitor type 1 protein was downregulated, while miR-221 and miR-222 were significantly increased in gastric cancer tissues. Bioinformatic predictions and luciferase assay verified that the 3′-untranslated region of the HAI-1 gene is a direct target site for miR-221 and miR-222. Overexpression of miR-221 and miR-222 in MGC-803 cells leads to the inhibition of hepatocyte growth factor activator inhibitor type 1 protein expression, thus promoting cell proliferation and migration; whereas knockdown of miR-221 and miR-222 showed opposite effects. Moreover, we found that the expression level of hepatocyte growth factor activator protein was increased when hepatocyte growth factor activator inhibitor type 1 was knocked down in MGC-803 cells. Thus, gastric cancer is probably an autocrine tumor, and the antitumor mechanism of hepatocyte growth factor activator inhibitor type 1 in vitro might be mediated by regulating the expression of hepatocyte growth factor activator protein. Therefore, our data illustrated a novel pathway comprising miR-221and miR-222 and hepatocyte growth factor activator inhibitor type 1 in gastric cancer, which is a potential target for future clinical use.